OPTIMIZING SPORTS SHOES SELECTION: AN AHP APPROACH FOR EVALUATING PREFERENCES AND DECISION-MAKING FACTORS - Zurina Hanafi; Jun Cheng Loh (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
With increasing awareness of a healthy lifestyle, daily workouts have become essential for the lives of young adults in university. Consequently, sports shoes have become a necessary requirement in this situation. This paper explores the preference for sports shoes among Universiti Utara Malaysia (UUM) students. This study aims to analyse the attributes or important criteria that influence their choices and how much influence these factors have on students’ preferences in sports shoe selection. The Analytical Hierarchy Process (AHP) method was employed to evaluate the important factors and alternatives and identify the criteria and alternatives that best represent the preferences of UUM students. The four key criteria examined were price, comfort, design, and brand loyalty, with the three alternatives being Nike, Adidas, and Skechers. The results indicated that design is the most influential factor, followed by price, comfort, and brand loyalty. Among the brands, UUM students preferred Adidas, while Skechers was the least favoured. This study significantly enhances our understanding of the factors influencing UUM students’ sports shoes selection preferences, providing insight for better catering to the needs of this demographic.